Report on Vietnam Inception Workshop for CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) - International Livestock Research Institute; Alliance of Bioversity International and CIAT (International Livestock Research Institute, 2022)
The kick off workshop of the CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion (SAPLING)—took place on 20-21 April in Son La Province, Vietnam. The workshop was co-hosted by the Sub-department of Animal Health and Livestock Production and Fisheries, Son La Province (Sub-DAH), the International Livestock Research Institute (ILRI) and the Alliance for Bioversity International and CIAT (ABC). The workshop brought together about 80 key stakeholders from Son La province including local authorities, farmers, private sector actors and the research program team. This meeting was convened to enhance implementation of the SAPLING initiative. In the first day of the workshop, scientists shared an introduction to the SAPLING initiative and to the targeted value chains of pigs, beef and chicken. The country team then worked with partners to co-develop the Theory of Change (TOC) (aims, outcomes and priority innovation packages) for the coming three years, including priority sites for the initiative. In the second day of the workshop, participants reviewed and finalized the TOC (identify gaps, actors and assumptions), discussed plans to prioritize innovations using trade-off analysis and scaling readiness assessment, and agreed on the roles and responsibilities and a calendar of key activities.